Berge equilibrium in linear-quadratic mean-field-type games. Issue 15 (October 2020) - Toumi, Noureddine; Barreiro-Gomez, Julian; Duncan, Tyrone E.; Tembine, Hamidou
Abstract: In this paper, we study Berge equilibria in linear-quadratic mean-field-type game problems under a jump-diffusion-regime switching state dynamics that incorporate mean-field terms in both the states and cost functional. In the cost functional, we consider conditional variance of the states and control actions, conditional mean of states and control actions, and conditional covariance terms. The underlying Berge problem is solved in a semi-explicit way by using the direct method and an illustrative numerical example is presented.